DO EXTERNAL FACTORS AFFECT THE LEVEL OF TOURIST VISITS - Mubarrok, Wafiyulloh; Dewanti, Diah Setyawati; Purna, Fitra Prasapawidya (LPPM Universitas Jambi, 2025)
This study investigates the influence of external factors on tourist visits to ASEAN-6 countries (Indonesia, Thailand, Singapore, Malaysia, Vietnam, and the Philippines), renowned for their global appeal as tourist destinations. Employing a fixed effect panel data regression model, the research utilizes annual World Bank data from 2004 to 2020 to analyze the effects of political stability, inflation, airport availability, traffic accident rates, and currency exchange rates on tourist arrivals. The results reveal that political stability significantly increases tourist visits, as it enhances perceptions of safety and reliability. Inflation, conversely, negatively impacts tourism by reducing affordability. Surprisingly, airport availability has a negative effect, possibly due to stringent inspections that may discourage travelers. Traffic accident rates show a positive correlation, likely reflecting increased tourist activity in well-connected urban areas. Meanwhile, currency exchange rates exhibit no significant influence. The findings underscore the importance of addressing these external factors to improve the tourism sector in ASEAN-6 countries. Governments are encouraged to enhance regional cooperation, develop cross-border travel packages, and invest in public facilities to create a more tourist-friendly environment. However, the study acknowledges its limitations, such as excluding variables related to pandemics and environmental concerns, which are increasingly relevant in the tourism industry. Future research should incorporate these aspects to provide more comprehensive policy recommendations and support sustainable tourism growth.